The construction of heterosexism in young people’s discourse: the dilemma of “normality” and “rights” - Σαπουντζής, Αντώνης; Χατζηστεργίου, Μαργαρίτα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The study of prejudice against gay people became an important field of sociopsychological research in the last few years. A substantial body of research attempted to examine the negative, homophobic attitudes against gay people as well as the various variables that seem to be associated with homophobia. Although this research tradition has made an important contribution to the study of the phenomenon at hand, more recent approaches based on the turn to language in social psychology have emphasized the dilemmatic opinions in the society. The present article drawing on the research tradition of discourse analysis and ideological dilemmas, examines the way in which young people from a small town in North Greece construct homosexuality in discourse. It is argued that often participants on the one hand used various strategies in order to disclaim prejudice against gay people, while on the other hand they mobilized discourses against certain gay rights. These dilemmas are scrutinized in relation to the way they are mobilized and also in relation to the ideologies they seem to draw upon.